Mabādi’ ‘Asyarah as an Epistemological Framework for National Fiqh: Reconstructing Lirboyo’s Contemporary Islamic Legal Thought - Abdurrohman Kafabihi; Muhammad Rifa’i Bachrun (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – The philosophy of science seeks to formulate the conceptual foundations that define the identity, structure, and purpose of a scientific discipline. Within the Islamic intellectual tradition, this function is represented by Mabādi’ ‘Asyarah, a framework consisting of ten fundamental principles used to establish the scientific foundations of knowledge. While National Fiqh (Fiqh Kebangsaan) developed by Lirboyo Islamic Boarding School has gained scholarly attention in discussions on religious moderation, nationalism, and pesantren-based Islamic thought, its epistemological foundations remain insufficiently explored. This study aims to reconstruct the scientific structure of National Fiqh through the framework of Mabādi’ ‘Asyarah and to examine its position within contemporary Islamic legal studies. Methods – Employing qualitative library research, this study analyzes the three volumes of Fikih Kebangsaan published by Lajnah Bahtsul Masail (LBM) and HIMASAL, complemented by classical Islamic sources, contemporary scholarship, and literature on philosophy of science. Data were analyzed descriptively and analytically using the ten principles of Mabādi’ ‘Asyarah as the primary analytical framework. Findings – The findings demonstrate that Mabādi’ ‘Asyarah systematically constructs the epistemological identity of National Fiqh through its definition (al-ḥadd), object of study (al-mawḍū‘), sources of knowledge (al-istimdād), methodological orientation, and societal objectives (al-thamrah). The study further reveals that National Fiqh functions not merely as a practical response to socio-political challenges but as a contextual jurisprudential paradigm rooted in pesantren epistemology and oriented toward public welfare within the Indonesian nation-state. Research implications – This article contributes to contemporary Islamic legal studies by demonstrating how the classical framework of Mabādi’ ‘Asyarah can be employed to formulate a coherent epistemological model for contextual Islamic jurisprudence.